Optimizing the Management of Grassroots Reading Hub for the Development of Inclusive Learning Spaces for Rural Communities - Fatihin, Muhammad Khoirul; Sucipto, Sucipto; Purwito, Lasi; Raharjo, Kukuh Miroso (Universitas Negeri Padang, 2026)
This article examines participatory-based management strategies of Grassroots Reading Hubs, or Community Reading Parks (Taman Bacaan Masyarakat / TBM), in fostering inclusive learning spaces for rural communities from an adult learning perspective. Grounded in the andragogical principles of Malcolm Knowles, this study emphasizes self-directed learning, the use of participants’ lived experiences, and the practical relevance of learning activities. A qualitative case study approach was employed, using interviews, observations, and document analysis at TBM Rumah Inspiratif in Jombang Regency. The findings show that TBM optimization is achieved through a pentahelix collaboration involving government, academia, private sector, community, and media. Unlike conventional top-down instructional coaching models, this study highlights a community-led and experience-based learning approach that is adaptive to local needs. Program innovations, such as upcycled handicraft training and thematic literacy activities, demonstrate how andragogical principles are operationalized in practice. These initiatives transform TBMs from reading spaces into inclusive hubs for lifelong learning, skills development, and community empowerment. This study contributes by integrating participatory management with andragogical learning design, offering a contextual and sustainable model for grassroots literacy development in rural areas.